Optimized Analysis Method for Evaluating the Shear Strength Parameters of Rock Joint Surfaces - Yao Xiao; Huafeng Deng; Jingcheng Fang; Hengbin Zhang; Jianlin Li (Advances in Civil Engineering)
The results obtained from the mechanical test of rock samples inevitably suffer dispersion owing to discrepancies between test specimens. In view of these deficiencies, the present study proposes a method based on the empirical equation of shear strength developed by Barton to determine the shear strength parameters of joint surfaces using a single test specimen. This approach is then applied to optimize the analysis of multiple specimens. An analysis of experimental results verifies that the shear strength parameters of joint surfaces obtained by the proposed method can more accurately reflect the shear mechanics of multiple specimens than conventional multiple sample analyses; meanwhile, the results are reasonable and reliable. More importantly, the optimized method ensures the shear strength parameters are no longer affected by the sequence of specimens employed during shear test. The optimized analysis method eliminates the effect of differences between specimens and the influence of subjective factors on test results and therefore provides more realistic evaluations of shear strength parameters.